Legal duties, professional obligations or notional guidelines? Screening, treatment and referral of domestic violence cases in primary health care settings in South Africa - Lillian Artz; Talia Meer; Gray Aschman (AOSIS, 2018)
Background: Since 2013, approximately 4400 women have been murdered by their partners in South Africa. This is five times higher than the per capita global average. Domestic violence is known to be cyclical, endemic and frequently involves multiple victims. It also becomes progressively more dangerous over time and may lead to fatalities. In 2012, the Health Professions Council of South Africa released a domestic violence protocol for emergency service providers. This protocol, or screening guidelines, includes assessing future risk to domestic violence, providing physical and psychosocial care, documentation of evidence of abuse and informing patients of their rights and the services available to them. The extent to which these guidelines have been circulated and implemented, particularly by general health care practitioners (HCPs), is unknown. Aim: We review international treaties to which South Africa is a signatory, as well as national legislation and policies that reinforce the right to care for victims of domestic violence, to delineate the implication of these laws and policies for HCPs. Method: We reviewed literature and analysed national and international legislation and policies. Results: The 'norms' contained in existing guidelines and currently practiced in an ad hoc manner are not only compatible with existing statutory duties of HCPs but are in fact a natural extension of them. Conclusion: Proactive interventions such as the use of guidelines for working with victims of domestic violence enable suspected cases of domestic violence to be systematically identified, appropriately managed, properly referred, and should be adopted by all South African HCPs.